(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
Due to the constantly changing economic situation in the world, company executives constantly have to look for ways to increase profitability. This article discusses various ways to increase the profitability of an enterprise. The importance of the company’s profitability indicator in modern market conditions was also noted. The impact of factoring, leasing, income from rental of property on profitability is given. The importance of the activities carried out by the company, which help to achieve the success of its development, is revealed.